2023
DOI: 10.1364/ol.487587
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pulse compression to sub-two-cycle, 1.3 mJ pulses at 1.9 μm wavelength with 132 W average power

Abstract: We report the nonlinear pulse compression of a high-power, thulium-doped fiber laser system using a gas-filled hollow-core fiber. The sub-two cycle source delivers 1.3 mJ pulse energy with 80 GW peak power at a central wavelength of 1.87 μm and an average power of 132 W. This is, so far, to the best of our knowledge, the highest average power of a few-cycle laser source reported in the short-wave infrared region. Given its unique combination of high pulse energy and high average power, this laser source is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The chosen compressor in terms of fused silica turns out to be an excellent compression scheme in this wavelength regime due to its ease of implementation and adjustment. A recent publication of Wang et al demonstrated that this compression approach allows compression (in combination with waveguide based spectral broadening) down to 10 fs [14]. However, the potential for further pulse compression might be limited by the higher-order dispersion exhibited by fused silica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chosen compressor in terms of fused silica turns out to be an excellent compression scheme in this wavelength regime due to its ease of implementation and adjustment. A recent publication of Wang et al demonstrated that this compression approach allows compression (in combination with waveguide based spectral broadening) down to 10 fs [14]. However, the potential for further pulse compression might be limited by the higher-order dispersion exhibited by fused silica.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve further pulse shortening, pulse post-compression is essential. State-of-the-art nonlinear pulse compression in the SWIR spectral region is realized employing thin plates or waveguide based approaches, such as normal dispersion fibers or noble-gas-filled hollow-core fibers or capillaries [13,14]. However, multi-pass cells (MPCs) with a nonlinear element or gas have recently been proven as an alternative approach for nonlinear post-compression, providing high throughput efficiency, excellent beam quality preservation, spatially homogenized spectral broadening as well as being insensitive to beam-pointing and beam-profile variations [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%